THE ISSUE OF IMPROVING THE CLASSIFICATION OF DIALECTISMS IN EXPLANATORY DICTIONARIES (TAMADDUN NURI JURNALI, 2024)
This article discusses the issue of improving the classification of dialectisms in explanatory dictionaries. The article also touches upon the formation and development of existing languages.